LITARARY TOURISM AND ITS DEVELOPMENT TRENDS - Azizova, Nazira; Akhmedova, Sabina (University Research Base, 2025)
Literary tourism has emerged as a significant niche within cultural tourism, attracting travelers interested in exploring locations associated with authors, literary works, and book culture. This paper examines the current state and future prospects of literary tourism, analyzing key trends such as digitalization, sustainable practices, and personalized experiences. The study highlights the economic and cultural impacts of literary tourism while addressing challenges related to overtourism and authenticity. Findings suggest that literary tourism will continue evolving through technological innovations and community-based initiatives, offering substantial benefits to local economies and cultural preservation efforts.